A Comprehensive Visualization and Comparative Analysis of Domestic and International Healthy Cities Research - Dan LUO; Chen WANG; Zhiguang DUAN (Yixue yu zhexue)
Since the 1990s, the study of healthy cities has emerged as a global field of study, with significant implications for public health development. Exploring the domestic and international trends in this area is essential for understanding the current research landscape and identifying future directions. The study takes the Web of Science Core Collection and CNKI as sources for English and Chinese publications, respectively. By applying CiteSpace and VOSviewer for visualization analysis, it compares the research foundations, hotspots, and evolutionary trends of healthy cities studies over the past three decades. The findings reveal significant disparities in research foundations, notable differences in research hotspots, and divergent evolutionary patterns between domestic and international studies. Finally, it is proposed that future research on healthy cities in China needs to deepen national and institutional exchanges and promote regional cooperation, enhance multidisciplinary collaboration, expand the scope and depth of research, pursue a balanced approach that integrates both inclusivity and distinctiveness in development.